The Entrepreneurial Intention Among Indonesian College Students During The COVID-19 Pandemic: Based On Psychological Capital - Titi Nugraheni; Misdiyono Misdiyono (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to empirically examine the relationship between psychological capital and entrepreneurial intention during the COVID-19 pandemic among Indonesian students. The respondents were 205 students from various universities and majors, aged 19-24. This research method uses primary data and quantitative descriptive data analysis using multiple linear regression. The Psychological Capital Questionnaire (PCQ) and Entrepreneurial Intention Questionnaire (EIQ) were used to measure the psychological capital scale, which includes self-efficacy, optimism, hope, resilience, and entrepreneurial intention. The findings of this study indicate a positive relationship between psychological capital and entrepreneurial intention among Indonesian students during the COVID-19 pandemic.